2013
DOI: 10.1016/j.ydbio.2013.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of fbxl10/kdm2bb rescues chd7 morphant phenotype in a zebrafish model of CHARGE syndrome

Abstract: CHARGE syndrome is a sporadic autosomal-dominant genetic disorder characterized by a complex array of birth defects so named for its cardinal features of ocular coloboma, heart defects, choanal atresia, growth retardation, genital abnormalities, and ear abnormalities. Approximately two-thirds of individuals clinically diagnosed with CHARGE syndrome have heterozygous loss-of-function mutations in the gene encoding chromodomain helicase DNA-binding protein 7 (CHD7), an ATP-dependent chromatin remodeler. To exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 50 publications
3
39
1
Order By: Relevance
“…By 4 days postfertilization (dpf), the GI tract has developed functionally and structurally into an intestinal bulb, midgut, and hindgut, and demonstrates anterograde and retrograde peristaltic movements, consistent with mature motility patterns . chd7 knockdown using morpholinos recapitulates a CHARGE‐like phenotype in zebrafish larvae, including smaller eyes and defects of the heart, otoliths, developing vertebrae, craniofacial cartilage, and segmental blood vessels . Interestingly, these chd7 morphant larvae also show deformities in the branchiomotor neurons of the hindbrain, as well as decreased projection of the trigeminal (CNV) and facial (VII) nerves .…”
Section: Introductionmentioning
confidence: 94%
“…By 4 days postfertilization (dpf), the GI tract has developed functionally and structurally into an intestinal bulb, midgut, and hindgut, and demonstrates anterograde and retrograde peristaltic movements, consistent with mature motility patterns . chd7 knockdown using morpholinos recapitulates a CHARGE‐like phenotype in zebrafish larvae, including smaller eyes and defects of the heart, otoliths, developing vertebrae, craniofacial cartilage, and segmental blood vessels . Interestingly, these chd7 morphant larvae also show deformities in the branchiomotor neurons of the hindbrain, as well as decreased projection of the trigeminal (CNV) and facial (VII) nerves .…”
Section: Introductionmentioning
confidence: 94%
“…Analysis of calcium signaling suggested that Cib2 is required for hair cell specification and function, possibly through the regulation of Ca 2+ in mechanotransduction and calcium homeostasis (Riazuddin et al, 2012). Analysis of the morpholino-injected embryos (morphants) showed otolith abnormalities, semicircular canal defects, and a circling swimming behavior (Patten et al, 2012;Balow et al, 2013). As for Harmonin, the Clarin-1 knockout mouse has no retinal phenotype, and so it is hoped that a zebrafish model for Ush3A will shed light on the role of Clarin-1 in this tissue (Phillips et al, 2013).…”
Section: Syndromic Disordersmentioning
confidence: 99%
“…Phillips and colleagues have reported the expression of clarin-1, the causative gene for Ush3A, in sensory cells of the ear, lateral line, and retina of the zebrafish. A general role in control of cell proliferation has been proposed, where the morphants show a reduction in proliferation that can be rescued by inhibiting the rRNA regulator fbxl10 (Balow et al, 2013). CHARGE syndrome (ocular coloboma, heart defects, choanal atresia, growth retardation, genital and ear abnormalities) affects many organ systems and is associated with mutations in the chromodomain-containing, ATP-dependent chromatin remodeller CHD7.…”
Section: Syndromic Disordersmentioning
confidence: 99%
“…In kismet mutant flies, RNA polymerase II transcriptional elongation is abnormal, suggesting another potential avenue for intervention [33]. Work in zebrafish has also uncovered deficits in ribosomal RNA dysgenesis, and overlapping functions between kismet/CHD7 and other genes that contribute to other craniofacial conditions, including Treacher-Collins syndrome [35,36]. Studies on Xenopus laevis also showed that neural crest derivatives are sensitive to changes in Chd7 dosage and exhibit CHARGE-like features, providing yet another potential route for early developmental intervention [37].…”
Section: Introductionmentioning
confidence: 99%